Reality and ideality in Víctor Andrés Belaunde’s «La crisis presente» - Katayama Omura, Roberto Juan (Mercurio Peruano, 2016)
At the opening of the academic year of 1914, Víctor And´rés Belaunde (1883-1966) pronounced in the old cloisters of the National University of SAn Marcos, his most celebrated speech entitled "The Current Crisis", having as audience the elite of Peruvian Academy as well as the highest authorities of Peru at the time, including the President of the Republic himself. No soubt that Peru lived in those timesfateful hour product of political and fiscal instability. And this is precisely what motivated Belaunde to draw the attention of the intellectual and political elites in the distant chronologically but essentially close year of 1914. The article investigates how Belaunde conceptualizes Peruvian reality of the time, which he considers had been the causes which had led them to the crisis to which he referred and what measures should have been taken to be out of the problem and go on the path of social progress. It is precisely this contrast between what he believes is the reality of the times and what it should be, which will allow us to distinguish between reality and ideality which is taking shape in his speech.